Alf Ross on Practical Reason - ZALUSKI, Wojciech (Utopía y Praxis Latinoamericana, 2016)
In his early work Kritik der Sogenannten Praktischen Erkenntnis. Zugleich Prolegomena zu Einer Kritik der Rechtswissenschaft the eminent Danish legal philosopher Alf Ross intended to provide the philosophical foundations for the construction of his theory of law. The central element of these foundations is his critique of practical reason (practical cognition). The purpose of this paper is to evaluate this critique. It is argued that in his analysis Ross oscillates between two different understandings of practical reason. According to the first one, practical reason is a special capacity to cognize and establish the objectively existing moral norms (values, or ends); according to the second one, it is a special capacity just to cognize the objectively existing moral norms (values, or ends). It is argued that his most interesting and plausible arguments (pointing at logical inconsistencies) against practical reason apply only to the former understanding thereof, not to the latter. Accordingly, his work fails to provide conclusive reasons for rejecting the concept of practical reason as a special capacity for the cognition of the objectively existing moral norms (values, or ends).